ORGANOLEPTIC QUALITIES OF FRESH, CHILLED, AND FROZEN BEEF - B.B., Lebang; Sriyani, N.L.P.; Sumardani, N.L.G. (Jurnal Peternakan Tropika, 2023)
Beef is one of the sources of animal protein that is easily damaged. Therefore, preservation is needed to ensure that beef is not easily damaged. One of which is preservation at low temperatures. The objective of this study was to determine organoleptic qualities of fresh, chilled, and frozen bali beef. The research was conducted in March 2022, at the Laboratory of Livestock Product Technology and Microbiology, Faculty of Animal Husbandry Udayana University. Chilling and freezing processes were carried out at the abattoir in Mambal, Abiansemal, Badung Regency, Bali. The design used was Completely Randomized Design (CRD) with 3 treatments and 7 replications. The treatments consisted of P1: fresh beef, beef stored for less than one day at room temperature (27 – 300C); P2: chilled beef, beef stored for two days at refrigerator temperature (0 – 50C); and P3: frozen beef, beef stored for two days at freezer temperature (-20 – -300C). The variables observed in this study were organoleptic qualities which included color, aroma, texture, flavour, tenderness, and overall acceptance. The result showed that the condition of bali beef had effects on color, aroma, flavour, tenderness, and overall acceptance, but had no effect on texture. Based on the results of this study, it can be concluded that fresh, chilled, and frozen bali beef have different organoleptic qualities. Keywords: Beef, bali cattle, organoleptic quality